Representation and Meaning of Space According to Metaphysical Architecture - Iis Septianingrum; Eny Irmawati; Fairuz Mutia (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
A space in architecture always has a different representation and meaning, according to what the architect who designed the space of an architecture wanted to convey. Along with the development of the world, architecture has also undergone several changes. These changes require the Architect to follow the demands of the market without considering other elements in the architecture, one of which is the element of metaphysics. Which is one of the important elements in architecture. As stated by Lorens Bagus 1996,